2022
DOI: 10.1037/dev0001292
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Chinese immigrant parents’ beliefs about children’s social development through play: A mixed methods explanatory sequential study.

Abstract: Currently, despite the rapid growth of the population of Chinese immigrant families and children in the United States, preschool-aged Chinese-heritage children are an underrepresented group in research. The overarching purpose of this project was to provide a deeper understanding of Head Start Chinese immigrant parents’ beliefs about children’s social-emotional development, the value of play during the preschool period, and the potential role of cultural orientation. The study followed the steps of a mixed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In the context of migrant children in urban China, www.co-psychiatry.com their marginalized socio-economic status -resulting from being rural or nonlocal Hukou holdersmay further exacerbate their risk of loneliness. Additionally, childhood, a crucial developmental stage for learning to connect with others and form interpersonal relationships [61], may amplify the negative impact of internal migration on the social connectedness of migrant children. This is particularly true for those in their prepuberty phase due to their increased vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of migrant children in urban China, www.co-psychiatry.com their marginalized socio-economic status -resulting from being rural or nonlocal Hukou holdersmay further exacerbate their risk of loneliness. Additionally, childhood, a crucial developmental stage for learning to connect with others and form interpersonal relationships [61], may amplify the negative impact of internal migration on the social connectedness of migrant children. This is particularly true for those in their prepuberty phase due to their increased vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to exploratory sequential studies, fewer explanatory sequential studies detail if or how the second phase (qualitative) builds from the first (quantitative). Even when other elements of a quality mixed methods study are reported, such as the intent of a design, details about how building integration is accomplished are not often described (e.g., Hyun et al, 2022; Thornberg et al, 2022). This gap in the explanatory sequential literature is widened when considering added complexity from applying a participatory qualitative phase (i.e., participants driving research processes), since the explanatory design is typically found to be quantitatively driven (Morgan and Hoffman, 2021).…”
mentioning
confidence: 99%